2020
DOI: 10.1038/s42003-020-01410-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of resolvin D1 and antibiotics with nanovesicles to lungs resolves inflammation and clears bacteria in mice

Abstract: Resolution is an active process that protects the host damage from inflammation responses induced by infections. Simultaneously resolving inflammation and eliminating pathogens may be effective to treat infectious diseases, but it is required to deliver therapeutics to infectious sites. Here, we proposed a strategy to incorporate RvD1 and an antibiotic (ceftazidime) in human neutrophil-membrane derived nanovesicles that can specifically target inflamed vasculature for treatment of lung infection caused by P. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…Nanovesicles from neutrophils can specifically target inflamed endothelium in brain and lungs in order to treat stroke and acute lung inflammation (Dong et al, 2019 ; Gao et al, 2020 ). Nitrogen cavitation can rapidly disrupt cells to form pure nanovesicles from cell membrane (Gao et al 2016 ).…”
Section: Preclinical Studies Of Cell Membrane-camouflaged Biomimetic Nanoparticles Against Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanovesicles from neutrophils can specifically target inflamed endothelium in brain and lungs in order to treat stroke and acute lung inflammation (Dong et al, 2019 ; Gao et al, 2020 ). Nitrogen cavitation can rapidly disrupt cells to form pure nanovesicles from cell membrane (Gao et al 2016 ).…”
Section: Preclinical Studies Of Cell Membrane-camouflaged Biomimetic Nanoparticles Against Inflammationmentioning
confidence: 99%
“…In one study, incorporating resolvin D1 into the lipid bilayer of neutrophil membrane allowed such nanovesicles to adhere specifically to endothelial cells for the treatment of ischemic stroke lesions and lung infection (Gao et al, 2021). Resolvin D1 blocks infiltration by neutrophils and promotes the clearance of macrophages, helping to resolve inflammation (Gao et al, 2020(Gao et al, , 2021. These studies demonstrate that neutrophil membrane nanovesicles possess significant therapeutic potential for the treatment of inflammatory disorders.…”
Section: Nanoparticles Coated With Neutrophil Membranementioning
confidence: 99%
“…Application of exogenous RvD1 reduced both bacterial growth and neutrophil infiltration, in both acute and long-term murine models of pneumonia [ 173 ]. While further studies of the therapeutic potential of resolvins are required in humans, these findings suggest that RvD1 may be a plausible therapeutic target in treating bacterial pneumonia due to its role in inhibiting inflammation and enhancing tissue healing in murine lung models [ 277 , 278 , 279 , 280 ]. To date, no human clinical trials with resolvins have been reported, but these compounds are well tolerated in mice [ 281 ].…”
Section: Therapeutic Interventions That Manipulate Efferocytosismentioning
confidence: 99%
“…This study reveals a new strategy to treat infectious diseases by designing nanoparticles to target inflammatory pathways and pathogens. ( Gao et al, 2020b ) ( Table 1 ).…”
Section: Resolvin D1 In Different Models Of Ardsmentioning
confidence: 99%